Influencing factors on the tensile properties of selective laser melting 3D printing AlSi10Mg - WANG Yong-hui; HU Qiang; ZHANG Jin-hui; LIU Ying-jie; SHENG Yan-wei; ZHAO Xin-ming (Fenmo yejin jishu)
The tensile properties of the selective laser melting (SLM) 3D printing AlSi10Mg samples were investigated which were prepared by the different forming processes, raw powders, and heat treatments. The influencing factors on the tensile properties of SLM 3D printing AlSi10Mg samples were discussed in this paper, including 3D printing forming process, powder physical properties, and heat treatment system. The results show that, the laser energy density affects the relative density of the AlSi10Mg samples, which influences the tensile properties deeply. The holes are mostly distributed at the junction and on the bottom of molten pool when the laser energy density is low, and the over high energy density leads to the distribution of pores inside the molten pool. The AlSi10Mg samples prepared using the powders with high sphericity can achieve the better tensile properties due to the good physical properties and low hollow powder ratio. The Si phase coarsens gradually as the annealing temperature increases from 270 ℃ to 300 ℃, leading to the decrease of strength and the increase of elongation gradually.